Diving deeper into the underlying white shark behaviors at Guadalupe Island, Mexico. Issue 21 (18th October 2021) - Aquino‐Baleytó, Marc; Leos‐Barajas, Vianey; Adam, Timo; Hoyos‐Padilla, Mauricio; Santana‐Morales, Omar; Galván‐Magaña, Felipe; González‐Armas, Rogelio; Lowe, Christopher G.; Ketchum, James T.; Villalobos, Héctor
Abstract: Fine‐scale movement patterns are driven by both biotic (hunting, physiological needs) and abiotic (environmental conditions) factors. The energy balance governs all movement‐related strategic decisions. Marine environments can be better understood by considering the vertical component. From 24 acoustic trackings of 10 white sharks in Guadalupe Island, this study linked, for the first time, horizontal and vertical movement data and inferred six different behavioral states along with movement states, through the use of hidden Markov models, which allowed to draw a comprehensive picture of white shark behavior. Traveling was the most frequent state of behavior for white sharks, carried out mainly at night and twilight. In contrast, area‐restricted searching was the least used, occurring primarily in daylight hours. Time of day, distance to shore, total shark length, and, to a lesser extent, tide phase affected behavioral states. Chumming activity reversed, in the short term and in a nonpermanent way, the behavioral pattern to a general diel vertical pattern. Abstract : This study linked horizontal and vertical movements of white sharks from active tracking data and obtained six different behavioral states through the use of hidden Markov models.